Post-treatment control or treated controllers? Viral remission in treated and untreated primary HIV infection - Martin, G; Gossez, M; Williams, J; Stöhr, W; Meyerowitz, J; Leitman, E; Goulder, P; Porter, K; Fidler, S; Frater, J; SPARTAC Trial Investigators (Lippincott, Williams & Wilkins, 2017)
OBJECTIVE(S): An HIV cure will impose aviraemia that is sustained following the withdrawal of antiretroviral therapy (ART). Understanding the efficacy of novel interventions aimed at curing HIV requires characterization of both natural viral control and the effect of ART on viral control after treatment interruption. DESIGN: Analysis of transient viral control in recent seroconverters in the Short Pulse AntiRetroviral Therapy at Acute Seroconversion trial. METHODS: We compared untreated and treated HIV seroconverters (n = 292) and identified periods of control (plasma HIV RNA < 400 copies/ml for ≥16 weeks off therapy) in 7.9% of ART-naive participants, and in 12.0% overall. HIV DNA was measured by qPCR, and HIV-specific CD8 responses were measured by enzyme-linked immunosorbent spot assay (ELISpot). T-cell activation and exhaustion were measured by flow cytometry. RESULTS: At baseline, future controllers had lower HIV DNA, lower plasma HIV RNA, higher CD4 : CD8 ratios (all P < 0.001) and higher CD4 cell counts (P < 0.05) than noncontrollers. Among controllers, the only difference between the untreated and those who received ART was higher baseline HIV RNA in the latter (P = 0.003), supporting an added ART effect. CONCLUSION: Consideration of spontaneous remission in untreated individuals will be critical to avoid overestimating the effect size of new interventions used in HIV cure studies.